Uplift resistance of buried pipes anchored with geosynthetics. Issue 2 (1st April 2015) - Bernal, D.F.; Palmeira, E.M.
Abstract : ABSTRACT: Buried pipes are important components of the oil industry for the transportation of different types of fluids. Accidents with such pipes can cause severe damage to the environment and to neighbouring structures and, unfortunately not rarely, with the loss of human lives. Among others, the action of waves, buoyance and pipe bucking can cause undesirable vertical or lateral displacements of buried pipes. This paper examines the use of geosynthetics as anchorage of buried pipes. Model tests were carried out with different types of geogrids and anchorage arrangements. The results showed that the presence of the anchorage can increase maximum pipe uplift forces as much as 180% in comparison with the result obtained for the unanchored pipe. Equations for estimates of maximum uplift force for anchored pipes were developed and comparisons between predictions and measurements are presented and discussed. The results obtained show the potential use of geosynthetics to anchor buried pipes.